2015
DOI: 10.1016/j.ijcard.2014.12.045
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac effects of acute exhaustive exercise in a rat model

Abstract: Excessive physical activity has an adverse effect on the heart. The observed functional impairment is associated with increased nitro-oxidative stress, enhanced apoptotic signaling and dysregulation of the matrix metalloproteinase system after exhaustive exercise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
48
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 38 publications
7
48
0
2
Order By: Relevance
“…The authors showed elevated plasma levels of cardiac troponin T and creatinine kinase after exhaustive exercise, compared to controls, along with elevated nitro-oxidative stress, myocardium enhanced apoptotic signaling and dysregulation of the matrix metalloproteinase system [1]. In this line, Legaz-Arrese et al have investigated the influence of a mild endurance training program (14 weeks running, 3-4 days/week, 120-240 min/week, 65-85% of maximum heart rate) on exercise-induced increase of high-sensitivity cardiac troponin T (hs-cTnT) in humans, showing that both baseline and post-exercise hs-cTnT values after training were higher compared with pre-training and the response of the control group (P = 0.008) [2].…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The authors showed elevated plasma levels of cardiac troponin T and creatinine kinase after exhaustive exercise, compared to controls, along with elevated nitro-oxidative stress, myocardium enhanced apoptotic signaling and dysregulation of the matrix metalloproteinase system [1]. In this line, Legaz-Arrese et al have investigated the influence of a mild endurance training program (14 weeks running, 3-4 days/week, 120-240 min/week, 65-85% of maximum heart rate) on exercise-induced increase of high-sensitivity cardiac troponin T (hs-cTnT) in humans, showing that both baseline and post-exercise hs-cTnT values after training were higher compared with pre-training and the response of the control group (P = 0.008) [2].…”
mentioning
confidence: 96%
“…
Olah et al have recently shown adverse effects of exhaustive exercise on the heart in a murine model [1]. The authors showed elevated plasma levels of cardiac troponin T and creatinine kinase after exhaustive exercise, compared to controls, along with elevated nitro-oxidative stress, myocardium enhanced apoptotic signaling and dysregulation of the matrix metalloproteinase system [1].
…”
mentioning
confidence: 99%
“…The control group was given treatment proportional which swam for 20 minutes per day, five times a week, for six weeks. While overtraining group swam for one and half hour, twice a day, every day, for six weeks [26,27,28]. Last day of treatment, the rats in both groups, were sacrificed and the heart to be examined.…”
Section: Methodsmentioning
confidence: 99%
“…The most typical mechanism is ischemia, which can be modified by many factors, such as pre-conditioning 8 , post-conditioning 9,10 , length of ischemic insult, and rate of coronary obturation. Ischemia triggers the apoptotic cascade 11 , leading to the presence of detectable troponin fragments in apoptotic bodies 12 . Ischemia also initiates the release of troponin fragments from so-called "myocardial blebs" (ref.…”
Section: Methodsmentioning
confidence: 99%